Selected readings to accompany Getting agriculture moving - Borton, Raymond E. (New York : Agricultural Development Council, 1966)
These readings are most useful as discussion materials, to stimulate group thinking about the local problems of agricultural development in each country. The readings are seen as being useful general reading for agricultural officials and technicians in Asia, Africa, and Latin America.
Volume 1.
Includes bibliographical footnotes.
ne 03/05/2019
Loans
Keywords: Agriculture and state